Post-transcriptional regulatory feedback encodes JAK-STAT signal memory of interferon stimulation - Kalliara, Eirini; Kardynska, Malgorzata; Bagnall, James; Spiller, David G.; Müller, Werner; Ruckerl, Dominik; Śmieja, Jarosław; Biswas, Subhra K.; Paszek, Pawel (Frontiers in Immunology, 2022)
Immune cells fine-tune their responses to infection and inflammatory cues. Here, using live-cell confocal microscopy and mathematical modelling, we investigate interferon-induced JAK-STAT signalling in innate immune macrophages. We demonstrate that transient exposure to IFN-g stimulation induces long-term desensitisation of STAT1 signalling and gene expression responses, revealing a dose- and time-dependent regulatory feedback that controls JAK-STAT responses upon re-exposure to stimulus. We show that IFN-a/b1 elicit a different level of desensitisation from IFN-g, where cells refractory to IFN-a/b1 are sensitive to IFN-g, but not vice versa. We experimentally demonstrate that the underlying feedback mechanism involves regulation of STAT1 phosphorylation but is independent of new mRNA synthesis and cognate receptor expression. A new feedback model of the protein tyrosine phosphatase activity recapitulates experimental data and demonstrates the JAK-STAT network’s ability to decode relative changes of dose, timing, and type of temporal interferon stimulation. These findings reveal that STAT desensitisation renders cells with signalling memory of type I and II interferon stimulation, which in the future may improve administration of interferon therapy.